Comparison of Benign and Malignant Pilomatricomas Using Whole-exome Sequencing - YEO, MIN-KYUNG (Cancer Genomics Proteomics, 2020)
Background: Malignant pilomatricoma (MP) is a rare cancer of the hair matrix with only a few cases reported in literature. Given the rarity of this cancer and the lack of relevant genetic data, very little is known about the nature of the molecular pathophysiology except the involvement of the Catenin Beta 1 (CTNNB1)/Wnt/β-catenin signaling pathway in some cases. Materials and Methods: We describe the whole-exome genomic profiling of four samples from two patients: 1) an MP from patient I, 2) a coexisting benign pilomatricoma (BP) from patient I, 3) a BP from an age and location-matched control patient II, and 4) normal skin tissue from patient II. Results: We detected a pathogenic somatic missense mutation in fibroblast growth factor receptor 4 (FGFR4) (c.1162G>A, p. Gly388Arg) in MP and coexisting BP in patient I, whereas the control BP harbored the classical CTNNB1 mutant. Conclusion: This study, the first comparative analysis of benign and MP through whole-exome analysis, identified a novel oncogenic mutation in FGFR4.